2018
DOI: 10.1016/j.jor.2018.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Short term results of osteotomy-sparing technique in management of moderate hallux valgus using TightRope system

Abstract: Osteotomy-sparing technique using TightRope device is effective in the management of moderate hallux valgus provided that proper patient selection, adequate surgical technique, and proper postoperative protocol are followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…According to the pathogenesis of the hallux valgus proposed by Perera et al (2011), the medial deviation of the first metatarsal came before the lateral deviation of the 1st phalanx. Therefore, some surgical interventions aimed to stabilize the first metatarsal using different techniques (Wong et al, 2014a;ElAttar et al, 2018). Our study found that the manifestation of the first metatarsal medial deviation induced by deforming load may be hindered by the forefoot abduction or pronation that formed a viscous cycle to provoke more deforming load.…”
Section: Discussionmentioning
confidence: 81%
“…According to the pathogenesis of the hallux valgus proposed by Perera et al (2011), the medial deviation of the first metatarsal came before the lateral deviation of the 1st phalanx. Therefore, some surgical interventions aimed to stabilize the first metatarsal using different techniques (Wong et al, 2014a;ElAttar et al, 2018). Our study found that the manifestation of the first metatarsal medial deviation induced by deforming load may be hindered by the forefoot abduction or pronation that formed a viscous cycle to provoke more deforming load.…”
Section: Discussionmentioning
confidence: 81%
“…Also the application of two construct for every case can may lead, in our opinion to a more reliable and stable fixation with a decreased future risk for hardware failure, because of load sharing. [51][52][53][54][55] Relative novelty and progressive evolution of the technique have not yet established a steady learning curve and a stable set of rules in order to have conclusive overall results on the medium and long-term. Our experience shows that, at present time a good level of confidence can be maintained in this technique and its advantages but also we accept and support the need for further testing and analysis of results of homogenous case series.…”
Section: Resultsmentioning
confidence: 99%
“…A modern wave of techniques has reintroduced this concept by applying a dynamic, flexible fixation of a corrected IMA using high-strength suture wires secured on bone with metallic buttons or anchors (metallic or biodegradable). Also, variations of these procedures can be used for tarsometatarsal stabilization in conjunction with osteotomies for bone correction [48][49][50]. The results seem promising but a longer followup and biomechanical testing are needed for a comprehensive recognition as a reliable treatment strategy.…”
Section: Minimally Invasive and Novel Proceduresmentioning
confidence: 99%